AN ANALYSIS OF DIALOGUE SUBTITLES IN THE MOVIE "PRETTY WOMAN" - Hizkia Pertiwi, - (2010)
The research is entitled An Analysis of Dialogue Subtitles in the Movie "Pretty Woman". It aims to find out the procedures that are used by the translator to translate the dialogue in the movie and to investigate whether the subtitles fulfill the criteria of a good translation. Hence, a descriptive qualitative research method is used to provide good directions in properly examining the data collected (Fraenkel and Wallen, 1993). The study reveals that there are 1207 dialogue and 2062 sentences of the movie. Moreover, 400 samples of the sentences or words in the dialogue were taken to be analyzed in details. The translation procedures used in this study are proposed by Newmark (1988) and other experts, including Vinay and Darbelnet (2000), Hardin and Picot (1990, as cited in Zakhir, 1998), Catford (2000, as cited in Munday, 2001), Harvey (2000, as cited in Ordudari, 2008), and also Bayar (2007, as cited in Ordudari, 2008). These procedures are namely literal, transference, naturalization, cultural equivalent, functional equivalent, descriptive equivalent, synonymy, through-translation, shift or transposition, modulation, recognised translation, translation label, compensation, componential analysis, reduction and expansion, paraphrase, and couplets. From the analysis, there are two results in this study. First of all, which is to do with the translation procedures, it was found that there are 11 types of translation procedures, as follows: 73 (18.25%) literal, 17 (4.25%) transference, 12 (3%) naturalization, 24 (6%) cultural equivalent, 21 (5.25%) synonymy, 19 (4.75%) through-translation, 20 (5%) shift or transposition, 46 (11.5%) modulation, 111 (27.75%) reduction and expansion, 32 (8%) paraphrase, and 25 (6.25%) couplets. Secondly, about the fulfilment of the criteria of a good translation, the translation shows that the subtitles fulfill some of the criteria of a good translation that are stated by Tytler (1907), Nida (1964; 1971), Larson (1984), and Massoud (1988), in that the translated text is easily understood, gives a complete transcript of the original text's ideas and attitudes, preserves the original text's character of the style and manner, and represents the closest natural equivalent of the source-language text. It is recommended that further study be conducted to look more closely at the process of procedures of translation as well as the quality of translation of other texts.